Isolation, identification, and evaluation of sporulation ability of Bacillus clausii, Bacillus badius, and Bacillus amyloliquefaciens derived from fermented pineapple juice - Le, Nguyen Thanh Binh; Dao, Thi Thu Thao; Pham, Dao Huyen Trang; Ngo, Thi Cam Tuyen; Phan, Thanh Hoa; Dao, Xuan Khanh; Huynh, Bui Trang; Nguyen, Thi Hoai Thuong; Ngo, Kim Khue; Nguyen, Thi Tho; Nguyen, Thi Mong Diep (Hue University Journal of Science: Natural Science, 2025)
The genus Bacillus comprises a wide range of Gram-positive, endospore-forming bacteria that are well recognised for their robustness and persistence under environmental stress, making them suitable candidates for diverse biotechnological and industrial applications. This study aimed to isolate, identify, and evaluate the sporulation ability of B. clausii, B. badius, and B. amyloliquefaciens strains derived from naturally fermented pineapple juice. After 7 days of fermentation, microbial isolation yielded three distinct bacterial strains. On the basis of morphological characteristics and 16S rRNA region sequence analysis, the isolates QNUPAB1-CNSH, QNUPAB2-CNSH, and QNUPAB3-CNSH were identified as B. clausii, B. amyloliquefaciens, and B. badius, respectively. The sporulation capacity of these isolates was assessed under different culture conditions, namely three media (PGA, LB, and DSM) and two incubation temperatures (35 and 38 °C). All strains exhibited the ability to form endospores with enhanced sporulation observed in the PGA medium at 38 °C for B. claussi and at 35 °C for B. amyloliquefaciens, and B. badius. These findings highlight the potential of these Bacillus isolates as promising candidates for probiotic applications and the development of microbial bioproducts.